2020
DOI: 10.1080/14756366.2020.1838500
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of anticancer activities of 2- or 4-substituted 3-(N-benzyltriazolylmethyl)-13α-oestrone derivatives

Abstract: 2- or 4-Substituted 3- N -benzyltriazolylmethyl-13α-oestrone derivatives were synthesised via bromination of ring A and subsequent microwave-assisted, Pd-catalysed C(sp 2 )–P couplings. The antiproliferative activities of the newly synthesised brominated and phosphonated compounds against a panel of human cancer cell lines (A2780, MCF-7, MDA-MB 231) were investigated by means of MTT assays. The most potent compound, the 3- N -benzyltriazolylm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Having found functional groups responsible for the biological effect, we turned our attention to attach all crucial structural elements to the hormonally inactive 13α-oestrone core. As a result, certain derivatives were identified as dually acting agents, possessing both enzyme inhibitory and antiproliferative properties 20 , 55 . We demonstrated that a few of our potent anticancer compounds exert a direct effect on the tubulin-microtubule system by increasing the rate of tubulin polymerisation 50 , 52 , 55 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having found functional groups responsible for the biological effect, we turned our attention to attach all crucial structural elements to the hormonally inactive 13α-oestrone core. As a result, certain derivatives were identified as dually acting agents, possessing both enzyme inhibitory and antiproliferative properties 20 , 55 . We demonstrated that a few of our potent anticancer compounds exert a direct effect on the tubulin-microtubule system by increasing the rate of tubulin polymerisation 50 , 52 , 55 .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, certain derivatives were identified as dually acting agents, possessing both enzyme inhibitory and antiproliferative properties 20 , 55 . We demonstrated that a few of our potent anticancer compounds exert a direct effect on the tubulin-microtubule system by increasing the rate of tubulin polymerisation 50 , 52 , 55 . These compounds might give an important basis for the design of oestrone-based potent anticancer agents, lacking oestrogenic activity.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently described the development of a number of potential anticancer compounds based on the hormonally inactive 13α-oestrane core 32–34 , 37 , 45 , 46 . Modifications at C-3 influenced the cytostatic properties markedly.…”
Section: Resultsmentioning
confidence: 99%
“…Modifications at C-3 influenced the cytostatic properties markedly. Introduction of a triazole moiety seemed to be highly advantageous 33 , 46 . The 3-[{1-benzyl-1 H -1,2,3-triazol-4-yl}methoxy]-13α-oestrone derivative ( 21 ) displayed substantial antiproliferative action against human cancer cell lines of gynaecological origin, with IC 50 values in the range of 0.3‒0.9 μM ( Figure 1 ) 33 .…”
Section: Resultsmentioning
confidence: 99%
“…The group of 13α-estrone derivatives proved to be promising concerning their enzyme inhibitory and/or antiproliferative properties. However, their biological activity greatly depends on their structure [ 33 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. We have observed that the substitution pattern of ring A influences bioactivity markedly.…”
Section: Introductionmentioning
confidence: 99%